Elevated serum levels of macrophage migration inhibitory factor and stem cell growth factor β in patients with idiopathic and systemic sclerosis associated pulmonary arterial hypertension - K. Stefanantoni; I. Sciarra; M. Vasile; R. Badagliacca; R. Poscia; M. Pendolino; C. Alessandri; C.D. Vizza; G. Valesini; V. Riccieri (PAGEPress Publications, 2015)
Pulmonary arterial hypertension (PAH) can be idiopathic or secondary to autoimmune diseases, and it represents one of the most threatening complications of systemic sclerosis (SSc). Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine with proinflammatory functions that appears to be involved in the pathogenesis of hypoxia-induced PH. In SSc patients, high serum levels of MIF have been associated with the development of ulcers and PAH. Stem cell growth factor β (SCGF β) is a human growth factor that, together with MIF, is involved in the pathogenesis of chronic spinal cord injury. The aim of our study was to measure serum levels of MIF in patients with idiopathic and SSc-associated PAH. We enrolled 13 patients with idiopathic PAH and 15 with SSc-associated PAH. We also selected 14 SSc patients without PAH and 12 normal healthy controls, matched for sex and age. PAH was confirmed by right hearth catheterism (mPAP>25 mmHg). MIF and SCGF β levels were measured by ELISA. We found significantly higher circulating levels of MIF and of SCGF β in patients with idiopathic PAH (P=0.03 and P=0.004) and with PAH secondary to SSc (P=0.018 and P=0.023) compared to SSc patients without PAH. Higher levels of MIF were found in those patients with an higher New York Heart Association (NYHA) class (P=0.03). We can hypothesize that MIF and SCGF β are able to play a role in PAH, both idiopathic or secondary, and in the future they may be evaluated as useful biomarkers and prognostic factors for this serious vascular disease.